Pengaruh Pemberian Reward terhadap Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak Kelas X MAN 1 Mandailing Natal - Amira Aisyah Chaniago; Syamsiah Depalina Siregar (PT. Willy Print Art, 2026)
This study aims to determine the effect of reward giving on student learning outcomes in the subject of Aqidah Akhlak in class X MAN 1 Mandailing Natal. The research method used is quantitative with a quasi-experimental design, where the experimental group was given reward intervention in the form of praise, awards, or bonus marks, while the control group underwent learning as usual. The research instrument consisted of a test of Aqidah Akhlak learning outcomes and documentation of reward giving. The results showed that there was a significant difference between the experimental and control groups; students who received rewards achieved higher learning outcomes than the control group. This finding indicates that reward giving has the potential to improve learning outcomes in the subject of Aqidah Akhlak. It is concluded that teachers and madrasas should consider a reward giving system as part of a learning strategy to strengthen student learning outcomes.